A cross sectional study to assess the psychological morbidity (depression, anxiety, stress) among undergraduate medical students in Bangalore Medical College and Research Institute, Bengaluru - N., Ramya; N., Ramakrishna Reddy; S., Ranganath T.; V., Subathra (International Journal Of Community Medicine And Public Health, 2018)
Background: Mental health is an important factor in medical student’s career. But unfortunately many are suffering from some form of mental problems. Like other young adults, under graduate medical students are similarly vulnerable to turmoil due to academic and social stress which often hampers their education achievement. The objectives of the study were to assess the prevalence of psychological morbidity (depression, anxiety, stress) among under graduate medical students and to find the association of these psychological morbidity with personal data Methods: A cross sectional study was conducted at Bangalore Medical College & Research Institute, Bangalore among Under-graduates medical students during November 2016- January 2017. Sample Size was calculated to be 151. Data was collected using a self-administered, pre-designed, pre-tested anonymous questionnaire, DASS 42. Data was analyzed by descriptive statistics and chi-square test. Results: Out of 151 students, 80 (52.98%) were males and 71 (47.01%) were females. Out of 151, 64(42.38%) had some form of depression, 83 (54.96%) had some form of anxiety and 69 (45.69%) had some form of stress. Conclusions: It is important to detect medical students who suffer from psychological morbidity at an early stage, so that treatment in the form of counselling could be initiated.